2007
DOI: 10.1111/j.1468-1331.2006.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐polio syndrome patients treated with intravenous immunoglobulin: a double‐blinded randomized controlled pilot study

Abstract: Post-polio syndrome (PPS) is characterized by new muscle weakness, atrophy, fatigue and pain developing several years after the acute polio. Some studies suggest an ongoing inflammation in the spinal cord in these patients. From this perspective, intravenous immunoglobulin (IvIg) could be a therapeutic option. We performed a double-blinded randomized controlled pilot study with 20 patients to investigate the possible clinical effects of IvIg in PPS. Twenty patients were randomized to either IvIg 2 g/kg body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 22 publications
(25 reference statements)
1
50
0
3
Order By: Relevance
“…Two Class I studies evaluated IVIg efficacy in patients with postpolio syndrome. 29,30 The first study, a double-blind RCT, evaluated 142 patients with postpolio syndrome, most with severe weakness (Class IV or V based on the National Rehabilitation Postpolio Limb Classification). 29 The 2 primary outcome measures were improved strength of a muscle believed to be significantly affected by postpolio (25%-75% of normal for age and sex) and improved quality of life as measured by the Short Form-36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Class I studies evaluated IVIg efficacy in patients with postpolio syndrome. 29,30 The first study, a double-blind RCT, evaluated 142 patients with postpolio syndrome, most with severe weakness (Class IV or V based on the National Rehabilitation Postpolio Limb Classification). 29 The 2 primary outcome measures were improved strength of a muscle believed to be significantly affected by postpolio (25%-75% of normal for age and sex) and improved quality of life as measured by the Short Form-36.…”
Section: Discussionmentioning
confidence: 99%
“…30 There were 3 concurrent primary outcome measures: muscle strength as measured by fixed dynamometer on selected muscles, Fatigue Severity Scale, and pain as measured by visual analog scale and pain drawing instrument change at 3 months. The study showed that patients receiving IVIg had significantly improved pain levels at 3 months as compared with baseline; however, there were no effects on muscle strength or fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiologic studies show marked, but not restricted, involvement of the sensory fibres (Dalmau & Rosenfeld, 2008 In the study with highest power, a significant increase of mean muscle strength of 8.3% was reported after two IVIg treatment cycles during 3 months. Physical activity and subjective vitality also differed significantly in favour of the IVIG group (Farbu et al, 2007). Post-polio syndrome is a chronic condition.…”
Section: Paraneoplastic Sensory Neuronopathy (Ssn)mentioning
confidence: 93%
“…I tillegg ses ofte økende atrofi, økt trettbarhet og smerter. En av to randomiserte studier viste effekt av intravenøs IgGbehandling (totalt 2 g/kg) på muskelstyrke, fysisk aktivitet og subjektiv opplevelse av bedring (30), mens den andre studien viste bedring av smerter og livskvalitet, men ikke av pareser (31). Det er ikke utført langtidsstudier.…”
Section: Postpoliosyndromunclassified